Submarine cave hermit crabs (Crustacea: Decapoda: Anomura: Paguroidea) from three islands of the Ryukyu Islands, southwestern Japan - Osawa, Masayuki; Fujita, Yoshihisa (Zootaxa, 2019)
Hermit crab species are reported on the basis of specimens collected by recent faunal surveys in submarine caves of three islands (Ie, Okinawa, and Shimoji Islands) of the Ryukyu Islands, southwestern Japan. The material includes three species in three genera of Diogenidae and 11 species in four genera of Paguridae. Catapaguroides longior Komai, Yamada & Shirakawa, 2010 and Pylopaguropsis granulata Asakura, 2000, each previously known only from the holotype, are recorded with intraspecific morphological variation observed in the present specimens. Color and morphological variations of Pagurixus nomurai Komai & Asakura, 1995 are also discussed. The present specimens of Catapaguroides foresti McLaughlin, 2002, C. longior, and Pylopaguropsis granulata suggest that the three species prefer the sandy or silty substrate in the deeper inner sites of submarine caves rather than other cryptic habitats in coral or rocky reefs.